Higher Effective Oronasal versus Nasal Continuous Positive Airway Pressure in Obstructive Sleep Apnea: Effect of Mandibular Stabilization. Issue 4 (2014) - Kaminska, M; Montpetit, A; Mathieu, A; Jobin, V; Morisson, F; Mayer, P
Abstract : BACKGROUND: In some individuals with obstructive sleep apnea (OSA), oronasal continuous positive airway pressure (CPAP) leads to poorer OSA correction than nasal CPAP. The authors hypothesized that this results from posterior mandibular displacement caused by the oronasal mask. OBJECTIVE: To test this hypothesis using a mandibular advancement device (MAD) for mandibular stabilization. METHODS: Subjects whose OSA was not adequately corrected by oronasal CPAP at pressures for which nasal CPAP was effective were identified. These subjects underwent polysomnography (PSG) CPAP titration with each nasal and oronasal mask consecutively, with esophageal pressure and leak monitoring, to obtain the effective pressure (Peff) of CPAP for correcting obstructive events with each mask (maximum 20 cmH2 O). PSG titration was repeated using a MAD in the neutral position. Cephalometry was performed. RESULTS: Six subjects with mean (± SD) nasal Peff 10.4±3.0 cmH2 O were studied. Oronasal Peff was greater than nasal Peff in all subjects, with obstructive events persisting at 20 cmH2 O by oronasal mask in four cases. This was not due to excessive leak. With the MAD, oronasal Peff was reduced in three subjects, and Peff <20 cmH2 O could be obtained in two of the four subjects with Peff >20 cmH2 O by oronasal mask alone. Subjects' cephalometric variables were similar to published norms. CONCLUSION: In subjects with OSA with higher oronasal than nasal Peff, this is partially explained by posterior mandibular displacement caused by the oronasal mask. Combination treatment with oronasal mask and MAD may be useful in some individuals if a nasal mask is not tolerated.